Abnormal oesophageal motility in patients with chronic cough. Issue 8 (28th July 2003) - Kastelik, J A; Redington, A E; Aziz, I; Buckton, G K; Smith, C M; Dakkak, M; Morice, A H
Abstract : Background: Although gastro-oesophageal reflux is a recognised cause of chronic cough, the role of oesophageal dysmotility is unknown. The aim of this study was to determine the prevalence of abnormal oesophageal motility in a selected group of patients with chronic cough. Methods: Oesophageal manometry and 24 hour pH monitoring were performed in 43 patients with chronic cough, 34 of whom had symptoms suggestive of gastro-oesophageal reflux. Comparative manometric measurements were made in 21 healthy subjects. Results: Nine patients with chronic cough had normal manometry and 24 hour pH. Of the remaining 34 patients, 11 (32%) had abnormal manometry alone, five (15%) had abnormal 24 hour pH monitoring alone, and in 18 (53%) both tests were abnormal. Only one patient in the control group had manometric abnormalities. Conclusions: These results point to a previously unrecognised high prevalence of abnormal oesophageal manometry in patients presenting with chronic cough. Oesophageal dysmotility may therefore be important in the pathogenesis of cough in these patients.